2014
DOI: 10.1080/10901027.2014.905808
|View full text |Cite
|
Sign up to set email alerts
|

Examining Educators’ Knowledge, Beliefs, and Practices About Using Technology With Young Children

Abstract: Technology has been shown to foster children's motivation and interest in instructional materials. In addition, researchers have found that technology results in higher levels of student engagement and greater levels of comprehension. Researchers have also found that educators must have the knowledge and skills in technology necessary to effectively support their students. Much of the research examining educator knowledge and skills has centered at the K-12 level. The current study examines the technological k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…Attitude items indicate a fairly positive outlook, and the majority of professionals rate their proficiency as average or better. This is similar to previous research with parenting educators by the author [31,40] and early childhood teachers [35,50]. Family educators appear to be most motivated by the functions of what technology provides to them-ways to make learning more interesting, a way to organize resources, a means for connecting to others-and when resources are available to them.…”
Section: Family Educators' Technology Use: 'It Depends'supporting
confidence: 82%
“…Attitude items indicate a fairly positive outlook, and the majority of professionals rate their proficiency as average or better. This is similar to previous research with parenting educators by the author [31,40] and early childhood teachers [35,50]. Family educators appear to be most motivated by the functions of what technology provides to them-ways to make learning more interesting, a way to organize resources, a means for connecting to others-and when resources are available to them.…”
Section: Family Educators' Technology Use: 'It Depends'supporting
confidence: 82%
“…Although previous studies such as Blackwell et al (2013), Fenty and McKendry Anderson (2014), Plowman and Stephen (2005) and Wood et al (2008) have identified a lack of support and training as structuralist barriers to the integration of IT, they were not found to be present in this case study. In regards to support, the CEO stated that that "if there is an enthusiasm for the technology or delivering something in a program that is enhanced by the technology, we will step in and support that".…”
Section: Support and Trainingcontrasting
confidence: 65%
“…In their examination of iPad adoption and use in the tertiary educational sector, Murphy (2011) found previous technology exposure promoted uptake of the innovative IT devices. As the individualist perspective focuses on an individual's internal characteristics and traits, the literature on barriers to IT integration identified negative educator beliefs and attitudes (Fenty and McKendry Anderson 2014;Ihmeideh 2009;Joshi et al 2010;Li 2006;Lindahl and Folkesson 2012a;Tsitouridou and Vryzas 2004;Wood et al 2008), a lack of knowledge and skills (Edwards 2005;Fenty and McKendry Anderson 2014;Ihmeideh 2010;Leung 2003;Li 2006;Nikleia and Despo 2005;Parette et al 2013;Plowman and Stephen 2005;Tsitouridou and Vryzas 2004;Wood et al 2008), the age of the educator (Parette et al 2013;Ihmeideh 2010) and lack of confidence (Blackwell et al 2014;Fenty and McKendry Anderson 2014;Joshi et al 2010;Li 2006;Nikolopoulou and Gialamas 2013;Plowman and Stephen 2005;Tsitouridou and Vryzas 2004) as barriers to the IT appropriation process.…”
Section: Individualist Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This mismatch of STEM education in early childhood has caused early childhood teachers to avoid teaching STEM and thereby fail to develop their confidence to teach subjects related to STEM education in classrooms (Brown, 2005;Fenty and Anderson, 2014;Timur, 2012).…”
Section: Introductionmentioning
confidence: 98%